Gambaran Karakteristik Ibu Bersalin Dengan Berat Bayi Lahir Rendah (BBLR) Di RSUD Kota Bekasi Tahun 2012 - Royani Chairiyah; Rina Sari Marliaty (STIKes Persada Husada Indonesia, 2015)
Low birth weight (LBW) is when the baby's weight less than 2500 grams (up to 2499 grams). Babieswho are born with LBW are generally unable to reduce the new environmental pressures that can lead toweakened growth and development, even interfere with their survival (Prawirohardjo, 2006). This study usessecondary data to review maternal books with LBW status, maternal age, parity, double pregnant, andgestational age. The populations in this study were 196 women giving birth to LBWatBekasi City Hospital fromJuly 1, 2012 until July 12, 2013 and the sampling technique used by total sampling. This study is a descriptive,overview of women characteristics giving birth to low birth weight in the General Hospital of the City of Bekasi.Based on the results obtained fromBekasi City Hospital in 2012, 196 maternal LBW are divided into severalcategories, the highest LBW 1500-2500gram 168 newborns (85.7%), the incidence of maternal LBW mothers byage group, the highest frequency of 20-35 year-old mother, maternal 156 (79.6%), the incidence of maternalwith LBW based on parity, the highest frequency with parity multiparous mothers as many as 108 women givingbirth (55.8%), the incidence of maternal LBW pregnant by double as many as 42 newborns (21.4%), theincidence of birth mothers with LBW by Age Pregnancy , the highest frequency of 37-42 weeks gestational age of100 people (51%). Base on the resultfrom several variables. Agevariable, parity, double pregnant andgestational age had a gap between theory and research, while the LBW incidence wasin accordance with theoryand research. The researchers suggestedBekasi City Hospital toimprove maternal health services in LBW as areferral hospital which could reduce LBW in West Java. Keywords: mother maternity, LBW, age, parity, pregnant ganda, age pregnancy.